IMPLEMENTASI METODE WINDOW SHOPPING DALAM MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI KEKAYAAN BUDAYA INDONESIA BAGI SISWA KELAS IV SDN 3 PANEMBAHAN - Rani, Rani; Rahmawati, Rani,Nurul Alit Wulansari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims explore how effective the Project Based Learning (PjBL) model combined with the Window Shopping method is in improving student learning outcomes in IPAS, particularly on the topic of Indonesian Culture for Grade IV students at SD Negeri 3 Panembahan. The results that implementing PjBL model alongside the Window Shopping method was successful in engaging students actively in the learning process. This approach provided with meaningfull and relevant learning experiences. The improvement in learning outcomes is evident when comparing results across the pre-cycle, cycle I, and cycle II. In the pre-cycle, the average students score was only 28,8 with 0%. After was applied in cycle I, the averafe score is to 49,8 and 15% of students achieved mastery. In cycle II, there was a substantial improvement, with the average score increasing to 87,6 and 88% of students meeting the learning goals. These findings suggest that using the PjBL model with the Window Shopping methoed is an effective strategy for enchaning student achievement in learning about Indonesia’s rich cultural heritage.